Mapping the Research Landscape of Sustainable Palm Oil: A Bibliometric Analysis: Pemetaan Lanskap Penelitian Minyak Sawit Berkelanjutan: Analisis Bibliometrik - Helda Jaya Puspita; Amalia Dwi Marseva (Jurnal Ilmiah Inovasi, 2026)
The palm oil plantation sectors play essential role in Indonesia’s economy, supporting livelihoods and significantly contributing to national growth. Indonesia is also one of the world’s leading producers of palm oil. As global attention to sustainability issues of palm oil industry continue to rise, research in this area has grown as well. This study aims to map the landscape of research on sustainable palm oil using a bibliometric approach, with data sourced from Google Scholar and collected by Publish or Perish. The selected data were analysed using VOSviewer. The findings show that most studies on sustainable palm oil in Indonesia focus on certification and broader sustainability concerns. In particular, schemes such as Indonesia Sustainable Palm Oil (ISPO) and Roundtable on Sustainable Palm Oil (RSPO) emerge as a main themes in the literature, with many studies highlighting how certification is implemented, how it shapes industry sustainability, and how it connects to global policies and standards.